Collisional and thermal dissociation of J/ψ and ϒ states at the LHC - Aronson, Samuel; Borras, Evan; Odegard, Brunel; Sharma, Rishi; Vitev, Ivan (Physics letters. B, 2018)
We present new results for the suppression of high transverse momentum charmonium [J/ψ,ψ(2S)] and bottomonium [ϒ(1S),ϒ(2S),ϒ(3S)] states in Pb+Pb collisions at the Large Hadron Collider. Our theoretical formalism combines the collisional dissociation of quarkonia, as they propagate in the quark–gluon plasma, with the thermal wavefunction effects due to the screening of the QQ¯ attractive potential in the medium. We find that a good description of the relative suppression of the ground and higher excited quarkonium states, transverse momentum and centrality distributions is achieved, when comparison to measurements at a center-of-mass energy of 2.76 TeV is performed. Theoretical predictions for the highest Pb+Pb center-of-mass energy of 5.02 TeV at the LHC, where new experimental results are being finalized, are also presented.